Construction Of A Psychological Immunity Scale For Middle School Students - Aggab, Zineb عقاب,زينب; Aouine, Belkacem عوين,بلقاسم (University of Eloued جامعة الوادي, 2025)
Abstract: The present study was conducted with the objective of developing a psychological immunity scale tailored for middle school students and to ascertain its psychometric properties. The formulation of the scale adhered to rigorous procedures, resulting in a comprehensive instrument featuring 46 items distributed across six dimensions: religious commitment, problem-solving ability, goal orientation, self-confidence, positive thinking, emotional stability, and self-regulation. The scale was administered to a cohort of 180 students from the third and fourth years of middle school. The psychometric integrity of the scale was evaluated through face validity and internal consistency reliability, with reliability further assessed via the split-half method and the calculation of Cronbach's alpha coefficient. The findings revealed that the internal consistency across the various dimensions and the overall scale ranged from 0.88 to 0.92. The Guttman split-half coefficient was determined to be 0.95, while Cronbach's alpha for the entire scale was recorded at 0.81. These metrics indicate that the psychological immunity scale developed through this research exhibits robust signs of validity and reliability, affirming its psychometric solidity comparable to established scales.
Keywords: Psychometric Properties; Psychological Immunity